1990
DOI: 10.1159/000185969
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis of Membranoproliferative Glomerulonephritis Type I

Abstract: A b stra c t. We carried out a retrospective investigation in 220 patients to assess the influence of various parameters on the long-term course of membranoproliferative glomerulonephritis (MPGN) type 1.50 patients (23%) died during the follow-up period of 59 months on average, in another 57 (26%) end-stage renal failure developed. 54 patients (24%) suffered from chronic renal failure, stable renal function (creatinine below 1.3 mg/dl) was preserved in 59 patients (27%).5 years after biopsy 49% of the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…In systemic lupus erythematosus, for example, Esdaile et al (8) have shown that the factor most predictive of deterioration in renal function is the presence of interstitial involvement in the initial kidney biopsy. Similar observations have been made in IgA nephropathy (9, 10) and (11). Tubulointerstitial injury per se results in deterioration in renal function (1,12).…”
Section: Discussionsupporting
confidence: 74%
“…In systemic lupus erythematosus, for example, Esdaile et al (8) have shown that the factor most predictive of deterioration in renal function is the presence of interstitial involvement in the initial kidney biopsy. Similar observations have been made in IgA nephropathy (9, 10) and (11). Tubulointerstitial injury per se results in deterioration in renal function (1,12).…”
Section: Discussionsupporting
confidence: 74%
“…Despite the presence of clinical (hypertension, marked proteinuria) and histological (diffuse glomernlar involvement) features that have been associated with a poor outcome in other studies [2-4, 16, 17], our patients demonstrated significant clinical improvement. Although we lack an untreated control group for appropriate comparison, our results strongly suggest improved outcome in comparison to the natural history of the disease [2][3][4]. That this improvement was already evident after 3 months of therapy suggests that the initiation of therapy with intravenous methylprednisolone may promote early stabilization of the disease.…”
Section: Morphological Studiesmentioning
confidence: 96%
“…Approximately 50% of untreated patients will progress to end-stage renal failure within 10 years of onset [2][3][4]. Although several forms of therapy utilizing combinations of corticosteroids, antiplatelet agents, immunosuppressive drugs, and anticoagulants have been reported [5][6][7][8][9][10][11][12][13], the best form of therapy remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was similar to the previous reports. 15,16 In the literature, Cansick et al 16 reported that nephrotic syndrome at presentation is associated with a poor prognosis; this relation was previously published by Schwertz et al 11 and Somers et al, 17 as well. However, according to Cansick et al, the degree of proteinuria of patients without nephrotic syndrome did not predict the outcome.…”
Section: Discussionmentioning
confidence: 74%